Exploring the acid neutralizing effect in rainwater collected at a tropical urban area: Central Valley, Costa Rica - Esquivel-Hernández, Germain (2023)
We report on the chemical and the carbon isotopic composition of dissolved inorganic carbon (DIC) of rainwater collected between May and October 2020 in the Central Valley, Costa Rica. Precipitation samples were collected daily (N = 55) and analyzed for major ions, DIC, and δ13CDIC. Significant correlation (p < 0.05) between main acidic (SO42- and NO3- ) and major alkaline (Ca2+ and NH4+) species confirmed a very effective acid neutralization effect in rainwater (average pH: 5.90 ± 0.74). Significant temporal variations (p < 0.05) of δ13CDIC indicated the contribution of carbonate salts in rainwater from May to October but also CO2 dissolution at the beginning of the wet season (May), probably due to increased CO2 emissions from soil degassing. Temporal changes of Ca2+ neutralization factors followed the observed changes in δ13CDIC, which confirmed the high buffer capacity of precipitation in our study. HYSPLIT analysis also revealed long-range contributions of pedogenetic carbonates (e. g., Saharan dust) responsible for the acid neutralization capacity of rainwater (e.g., from July to September). Principal component analysis showed that four main factors explain 65% of the variance are: i) acid neutralization processes (Ca2+ neutralization factor), ii) marine salts (Cl- , Na+), iii) fossil fuels (SO42- , NO3- ), and iv) agriculture/fertilizers (NO3- , NH4+, K+). Our study demonstrated that a combined approach of chemical, isotope, and statistical analysis techniques can help unravel the mechanism of acid neutralization of rainwater in tropical urban areas. This information has strong implications for future studies related with the impact of acid deposition on ecosystem functioning, water quality, and infrastructure degradation.